Human Intervention Will Stabilize Groundwater Storage Across the North China Plain. Issue 2 (4th February 2022) - Yang, Wenting; Long, Di; Scanlon, Bridget R.; Burek, Peter; Zhang, Caijin; Han, Zhongying; Butler, James J.; Pan, Yun; Lei, Xiaohui; Wada, Yoshihide
Abstract: The North China Plain (NCP) has been subjected to groundwater overexploitation over the past decades as a result of rapid socioeconomic development and irrigation water demand with relatively limited renewable water resources. Operation of the middle route of the South‐to‐North Water Diversion Project (SNWD‐M) since December 2014 has provided an opportunity for groundwater sustainability in the NCP by increasing water supply and reducing groundwater abstraction. Water use changes have largely been driven by socioeconomic changes. However, impacts of water diversion, water use change, as well as climate variability in the future on groundwater storage (GWS) in the NCP have not been investigated. This study aims to simulate and project GWS in the NCP during 2005–2050 by incorporating effects of water diversion, water use, and climate variability. The high‐resolution Community Water Model with 30 arcsec spatial resolution was set up to assess interactions between water demand and availability by simulating surface water and groundwater abstraction dynamically. Results show that water diversion and reductions in water use may increase GWS over the NCP in 2050 by 144 mm (19 km 3 ) and 573 mm (75 km 3 ), respectively. Evaluation of GWS among different scenarios shows that combinations of factors, including water use reductions, water diversion, and precipitation variability can contribute up to 73%, 37%, and 32% to GWS stability, respectively. This study highlights the contributions of different management strategies toward sustainable GWS and the importance of water conservation along with diversions. Plain Language Summary: Human intervention (including water use reductions and water diversions) can stabilize groundwater storage in the North China Plain, which is among the most stressed aquifers globally and of great importance to food security in China. We found that water conservation (e.g., water use reductions) plays a more prominent role in groundwater stabilization than water diversions and climate variability. This has important implications for groundwater sustainability of heavily stressed aquifers globally. Regions considering large water diversion programs might reconsider the value of water conservation to address water‐resource issues, which is less costly and more environmentally benign. Key Points: The high‐resolution community water model coupled with a water diversion module was set up across the North China Plain Groundwater storage was simulated and projected until 2050 by incorporating effects of water use, water diversion, and climate variability Water use reductions, water diversion, and precipitation variability can contribute up to 73%, 37%, and 32% to groundwater storage stability